The effects of polyphenols and other bioactives on human health. Issue 2 (12th February 2019) - Fraga, César G.; Croft, Kevin D.; Kennedy, David O.; Tomás-Barberán, Francisco A.
Abstract : Consuming polyphenols is associated with benefits to cardiometabolic health and brain function, which are driven by their complex interrelationship with the gut microbiome, their bioactive metabolites, and other phytochemicals. Abstract : Although deficiencies in polyphenol intake do not result in specific deficiency diseases, adequate intake of polyphenols could confer health benefits, especially with regard to chronic diseases. Tea, cocoa, fruits, and berries, as well as vegetables, are rich in polyphenols. Flavan-3-ols from cocoa have been found to be associated with a reduced risk of stroke, myocardial infarction, and diabetes, as well as improvements in lipids, endothelial-dependent blood flow and blood pressure, insulin resistance, and systemic inflammation. The flavonoid quercetin and the stilbene resveratrol have also been associated with cardiometabolic health. Although polyphenols have been associated with improved cerebral blood flow, evidence of an impact on cognition is more limited. The ability of dietary polyphenols to produce clinical effects may be due, at least in part, to a bi-directional relationship with the gut microbiota. Polyphenols can impact the composition of the gut microbiota (which are independently associated with health benefits), and gut bacteria metabolize polyphenols into bioactive compounds that produce clinical benefits. Another critical interaction is that of polyphenols with other phytochemicals, which could be relevant to interpreting the health parameter effects of polyphenols assayed as purified extracts, whole foods, or whole food extracts.